2020
DOI: 10.1111/1471-0528.16524
|View full text |Cite
|
Sign up to set email alerts
|

Duration of estrogen exposure during reproductive years, age at menarche and age at menopause, and risk of cardiovascular disease events, all‐cause and cardiovascular mortality: a systematic review and meta‐analysis

Abstract: Background Little is known about the estrogen exposure measurement and mutual effect of age at menarche and age at menopause in the risk of cardiovascular disease (CVD) events. Objectives To evaluate estrogen exposure measurement and describe mutual effect of age at menarche and age at menopause in the risk of CVD events. Search strategy Systematic review of literature in PubMed, Embase and Web of Science for studies published up to 28 June 2020. Selection criteria Observational studies related to estrogen exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(67 citation statements)
references
References 55 publications
2
62
1
2
Order By: Relevance
“…51 These data are consistent across recent prospective studies. 46,[52][53][54] Other reproductive health variables associated with stroke risk include parity and breastfeeding. Data on parity suggest elevated stroke among women with ≥5 live births compared with 1 or 2 live births, though in some studies, adjusting for confounding variables, particularly body mass index, eliminated this association.…”
Section: Female-specific Risk Factorsmentioning
confidence: 99%
“…51 These data are consistent across recent prospective studies. 46,[52][53][54] Other reproductive health variables associated with stroke risk include parity and breastfeeding. Data on parity suggest elevated stroke among women with ≥5 live births compared with 1 or 2 live births, though in some studies, adjusting for confounding variables, particularly body mass index, eliminated this association.…”
Section: Female-specific Risk Factorsmentioning
confidence: 99%
“…However, only a few longitudinal studies have gone so far as to study associations between circulating sex hormone, sex hormone-binding globulin levels, and CVD, with varying results. 36 , 37 Moreover, as both menopause and biological aging are interrelated in time, the extent to which one contributes to age-related CV risk over the other is difficult to delineate. However, the question of a possible CV benefit from MHT has been promoted for decades, as noted in several observational studies such as the Nurse’s Health Study, which found postmenopausal hormone use to decrease risk for major coronary events in women without previous CVD.…”
Section: Menopause Hormone Therapymentioning
confidence: 99%
“…It seems intriguing that these two events in a woman’s reproductive life could be related. However, no consistent association between ages at menarche and menopause has been observed in epidemiological studies ( 2 , 48 , 49 , 50 , 51 ). This is further supported by newer genetic data revealing limited overlap in genomic regions associated with the timing of the two events ( 52 , 53 ).…”
Section: Discussionmentioning
confidence: 91%